Профилактические меры по обеспечению безопасных условий труда в производствах этилбензола-стирола - Mavrina L. N., Karimova L. K., Beigul N. A. (Relevant lines of scientific research: theory and practice, 2016)
This paper presents a comparative analysis of equipment used, the working conditions and health of workers in small and large scale manufacturing ethylbenzene-styrene. A set of preventive measures to improve working conditions in factories ethylbenzene-styrene.
Keywords: этилбензол-стирол; безопасные условия труда; Safe working conditions; ethylbenzene-styrene